Innovativeness as an Antecedents to Firm Supply Performance: The Mediating Role of Innovation Performance and Supply Chain Integration - Pongtep Phudetch; Aeknaree Toomphol; Naruemon Jituea; Patipol Homyamyen (International Journal of Supply Chain Management, 2020)
The study is planned to examine the impact of innovation on the SC performance of Indonesian manufacturing firms. Addition to that the study has examined the mediating role of innovation performance and SC performance in the relationship between the innovation ad SC performance of Indonesian textile manufacturing firms. 63.7% response rate was obtained for this survey. The influence of innovativeness on SC integration and SC performance has been empirically tested. The concept of innovativeness has emerged over some recent years and not much applied in the SC context. Therefore, there is a need for manufacturers to focus on innovativeness for improving SC integration and SC performance. There is rare evidence about the direct influence of innovativeness on SC performance. Innovativeness is an ability, which is based on action. Therefore, it cannot directly influence the performance of the SC. There is a need for carrying out practical operations, including SC integration for improving SC performance. This research is first of its nature in trying to explore the relationship in an integrated manner. Managers in the SC are assisted through innovativeness to improve information development and latest technologies. In this way, effectiveness of services and efficiency can be improved using innovation in business operations.